The Solution for Unstable Bubble Assets: Reflection from an Islamic Finance Perspective - Alatas, Muhamad Nagib (Universitas Islam Internasional Indonesia, 2023)
In the fast-paced world of technology, there exist popular investment instruments that have no intrinsic value (non-asset-based). As a result, their prices are highly volatile and prone to bubbles. However, from an Islamic perspective, investment vehicles must have a fundamental value (asset-based) to ensure price stability. This research aims to compare the behaviour of asset prices between non-asset-based and asset-based types by utilizing a system dynamics model. Furthermore, this study investigates the impact of two types of market sentiment: relatively stable good market and very good market sentiment, follows by very bad market sentiment. The findings of this study suggest that non-asset-based asset prices tend to bubble in response to good market sentiment and then rapidly decline when significant bad market sentiment arises. In contrast, asset-based assets tend to have more stable prices because investors have benchmarks and do not rely solely on intuition. This research highlights the importance of the fundamental value or asset base in investment instruments, as required by Islamic finance. However, asset-based assets can also be prone to high volatility when irrational investors dominate, and speculation prevails. In such cases, government intervention or regulation may be necessary to mitigate risks and stabilise the market.